The Effect of Urban Macroform on Urban Resilience: The Case of Düzce - Ecrin Kar; Selim Altuntaş; Hicran Hamza Çelikyay (Doğal Afetler ve Çevre Dergisi)
Türkiye has experienced many destructive earthquakes in its history. Düzce, located on the North Anatolian Fault line in the north-west of Türkiye, was shaken by two major earthquakes on August 17 and November 12, 1999. These earthquakes caused great loss of life and material damage in the city. The earthquake that occurred in Düzce on November 23, 2022 caused minor material damage. In this study, the city of Düzce will be analyzed in the context of spatial development and city development plans in the period from 1999 to 2023, and urban resilience assessment will be made through the city macro form. The aim of the study is to compare the effects of the zoning plans implemented after the 1999 earthquakes on the city after the 2022 earthquake and to measure urban resilience. Urban resilience analysis was prepared in ArcGIS software by evaluating the building stock, land potential, earthquakes, storey heights, population densities, open green area capacity, transportation network standards, proximity to fault lines, and soil structure in the area where Düzce city core was established. As a result, it was revealed that the urban macro form of Düzce shows low and medium level resilience. The results of the study reveal the critical importance of these measures for the city of Düzce. In line with the analyses, it is recommended to develop and implement policies that increase the resilience of the city.